Sustainable and ethical vicegerency in halal tourism practices - Saffinee, Siti Syahirah; Jamaludin, Mohammad Aizat; Rosli, Nur Liyana Izzaty; Amid, Azura; Hashim, Khairusy Syakirin Has-Yun (UUM Press, Universiti Utara Malaysia, 2024)
This paper investigates the sustainable and ethical vicegerency of Halal tourism and the Islamic principles influencing sustainable tourism, particularly in the context of Muslim travel. By conducting a literature review and case study analysis, the qualitative research design was implemented, involving a total of 10 informants. Additionally, successful programs and best practices that implement these concepts to enhance the sustainability of tourism destinations and experiences were investigated. The results indicate that there are components that can enhance the sustainability of tourism and the experiences of Muslim guests. The paper highlights the importance of incorporating Islamic themes into tourism sustainability frameworks to promote ethical and culturally sensitive behaviours. This paper provides governments and other tourism stakeholders with valuable insights into sustainable tourism programs that cater to the requirements of Muslim travelers and promote sustainability.